(3fXGe GdZQjHs - (3YjSi Hf EHQGgje GdQHYis; (3UGYO Hf GdMSf Hf YjSi GdQHYj GdHZOGOj, CHh GdYdGA,J (B417 (3g` s
(3ChdgG (B:s
(3GdMeO ddg eNQL GdCTjGA ef GdYOe Edi GdhLhO s
(3BNQgG (B:s
(3EPG LGA Vja LGA ddVja Vjajf aChOJ HeG JbQi GdVjha GdVGaf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdhQbI GdCNjQI HNW MOjKs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B186 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B318s
(3JHUQGJ GdCUd (B:s
Keywords: (3GddZIs